Frame type non-noble metal catalyst and preparation method thereof

By constructing the framework-type non-precious metal catalyst CuxFeyWO4, the shortcomings of existing catalysts in terms of catalytic performance and structural stability are solved, high activity, high stability and good selectivity are achieved, suitable for a variety of chemical reactions, and cost is reduced.

CN119746884APending Publication Date: 2025-04-04HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941740.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing catalysts have shortcomings in catalytic performance and structural stability, and it is difficult to break through the performance bottleneck of precious metal catalysts, and their ability to optimize the electronic state in structural design and active center is limited.

Method used

By preparing the MOF@POM complex and performing annealing, ion exchange and reduction processes, a framework non-precious metal catalyst, CuxFeyWO4, has a high active site density, large surface area and an optimized electronic environment.

Benefits of technology

The catalyst is achieved with high activity, high stability and good selectivity, and is especially suitable for chemical reactions such as oxidation, reduction and hydrogenation, which reduces costs and has good economic and sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746884A_ABST
    Figure CN119746884A_ABST
Patent Text Reader

Abstract

The invention relates to a framework type non-noble metal catalyst and a preparation method thereof, the catalyst comprises a framework type catalyst of CuxFeyWO4, x + y = 1, preferably x is 0.7, and y is 0.3. The preparation method of the catalyst comprises the following steps: S1, mixing and stirring copper salt, L-glutamic acid and phosphotungstic acid or a hydrate thereof in a solvent to prepare an MOF (at) POM compound; s2, annealing the MOF (at) POM compound in an inert gas atmosphere to prepare an MOF (at) POM derivative; and S3, dispersing the MOF (at) POM derivative in a ferric iron salt solution for ion exchange to prepare the frame type non-noble metal catalyst. The catalyst provided by the invention has a three-dimensional frame structure, large active site density, high specific surface area, and good catalytic performance and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a framework-type non-precious metal catalyst and a preparation method thereof. Background Art

[0002] In the chemical industry, catalysts are substances that accelerate the rate of chemical reactions without being consumed in the process. They play a vital role in production processes, especially in the fields of oil refining, plastic manufacturing, fertilizer production and environmental governance. With the increasing attention paid to environmental protection and resource efficiency, the development of new and efficient catalysts has become an important topic in the chemical industry.

[0003] In terms of catalyst design, the existing technology is still limited by the use of traditional materials and the limitations of synthesis methods. It is difficult to break through the performance bottleneck of precious metal catalysts, and the ability to fine-tune the catalyst structure and optimize the electronic state of the active center is limited. The structure of the catalyst plays a decisive role in its catalytic effect, and a reasonable structural design is very important for improving catalytic performance. By precisely controlling the coordination environment of the active center, the interaction between the catalyst and the reactant can be optimized, the electron transfer process can be improved, and the adsorption energy of key intermediates can be adjusted, thereby improving the catalytic activity of the catalyst for the target reaction and enhancing the stability and durability of the catalyst in harsh environments. At the same time, a reasonable structural design helps to improve the performance of non-precious metal catalysts, enabling them to replace traditional precious metal catalysts in multiple fields, achieve cost reduction and efficiency improvement, improve the economy and sustainability of the catalyst, and meet the needs of industrial applications.

[0004] In recent years, the development of efficient catalytic materials has been of great significance for promoting energy conversion and storage technologies, as well as the purification of polluted environments. As a new type of structural material, doped ordered framework materials (MOFs) have the advantages of large specific surface area, porosity, adjustable chemical bonds, and adjustable surface charge density, and can be applied to gas storage, gas adsorption, and catalysis. Therefore, the development of ordered framework material catalysts with high catalytic activity and stability is crucial for the field of energy conversion and storage.

[0005] In view of this, the present invention aims to develop a framework-type non-precious metal catalyst and a preparation method thereof, which has the advantages of multiple active sites and large surface area, and provides effective support for improving its catalytic performance. The above beneficial effects will help overcome the limitations of the prior art and provide an effective way to prepare high-efficiency catalysts. Summary of the invention

[0006] The main purpose of the present invention is to provide a framework-type non-precious metal catalyst and a preparation method thereof, so as to solve the problem of insufficient catalytic performance and structural stability of the catalyst in the prior art.

[0007] In order to achieve the above object, according to one aspect of the present invention, a framework-type non-precious metal catalyst is provided, which comprises Cu x Fe y A WO4 framework catalyst, wherein x+y=1, preferably x is 0.7 and y is 0.3.

[0008] According to another aspect of the present invention, a method for preparing a framework-type non-precious metal catalyst is provided, the method comprising the following steps: S1: mixing and stirring a copper salt, L-glutamic acid and phosphotungstic acid or a hydrate thereof in a solvent to prepare a MOF@POM complex; S2: annealing the MOF@POM complex in an inert gas atmosphere to prepare a MOF@POM derivative; S3: dispersing the MOF@POM derivative in a trivalent iron salt solution for ion exchange to obtain a framework-type non-precious metal catalyst.

[0009] Furthermore, in step S1, the molar ratio of copper to L-glutamic acid is in the range of 0.8 to 1.3, preferably 0.95-1.05; the molar ratio of copper to tungsten is in the range of 0.9 to 1.25, preferably 1.1-1.2.

[0010] Further, the copper salt is selected from one or more of copper acetate, copper chloride, copper bromide, copper nitrate and their hydrates, preferably the copper salt is selected from one or more of copper acetate and its hydrates;

[0011] Further, the solvent is selected from at least one of methanol, ethanol, acetone and water;

[0012] Furthermore, the ferric iron salt solution is selected from one or more of ferric nitrate, ferric sulfate and ferric chloride.

[0013] Further, in step S1, copper salt, L-glutamic acid and phosphotungstic acid or its hydrate are added to deionized water, wherein the concentration of copper is in the range of 0.01 mol / L to 0.03 mol / L, preferably 0.025 mol / L; stirring is performed, preferably the stirring time is 0.5 to 3 hours, more preferably 1 hour; an ethanol solution of trimesic acid is added to the stirred solution, preferably the concentration of the ethanol solution of trimesic acid is in the range of 0.01 to 0.03 mol / L, wherein the molar ratio of trimesic acid to copper salt is in the range of 0.66 to 1; stirring is performed, preferably the stirring time is 10 to 24 hours, more preferably 14 hours; the precipitate is collected, preferably by centrifugation or filtration; and then the precipitate is dried, preferably in a vacuum oven, preferably the drying temperature is 60° C. to 80° C., and preferably the drying time is 10 to 16 hours.

[0014] Further, in step S2, the MOF@POM composite is heated to 550-700°C, preferably 600-650°C, in an inert gas atmosphere, preferably the inert gas atmosphere is selected from nitrogen or argon, at a heating rate of 2°C / min to 10°C / min, preferably 5°C / min; maintained for 1 to 5 hours, preferably 2 hours; then cooled to room temperature at a rate of 2°C / min to 20°C / min; to obtain a MOF@POM derivative; preferably, the flow rate of the inert gas is in the range of 5 to 20sccm, preferably 10sccm.

[0015] Further, in step S3, the MOF@POM derivative is dispersed in a ferric iron salt solution, preferably the concentration of the ferric iron salt solution is 0.05M to 0.5M, and the concentration of the MOF@POM derivative in the ferric iron salt solution is 0.05g / L to 0.3g / L; stirring for 30 to 80 minutes, preferably 40 minutes, preferably stirring at a speed of 200-500rpm; reducing the MOF@POM derivative to obtain copper particles while completing ion exchange to form a framework-type non-precious metal catalyst; obtaining a precipitate, preferably by filtration or centrifugation; washing the precipitate, preferably using acetone or ethanol for washing, preferably washing at least three times; drying the precipitate, preferably placing it in a vacuum oven for drying, preferably the drying temperature is 60°C to 80°C.

[0016] According to another aspect of the present invention, there is provided a framework-type non-precious metal catalyst, characterized in that the catalyst is prepared according to the method according to any one of claims 2 to 9.

[0017] Furthermore, the main component of the catalyst prepared by this method is Cu x Fe y WO4, wherein x+y=1, preferably x is 0.7 and y is 0.3.

[0018] The present invention successfully constructs a novel framework-type non-precious metal catalyst Cu by preparing MOF@POM composite and subsequent annealing, ion exchange and reduction process. x Fe y WO4, the catalyst has high activity, high stability and good selectivity, and is particularly suitable for catalytic oxidation, reduction and hydrogenation chemical reactions. Its unique framework structure not only increases the surface area of ​​the catalyst and improves the catalytic efficiency, but also further optimizes the performance of the catalyst by controlling the ratio of elements. In addition, the use of non-precious metal materials significantly reduces the cost of the catalyst, which is conducive to large-scale industrial applications and is of great significance to environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 The flowchart of the preparation method of the framework-type non-precious metal catalyst of the present invention is shown.

[0021] Figure 2 A scanning electron microscope (SEM) image of the MOF@POM derivative of Example 1 of the present invention is shown.

[0022] Figure 3 A transmission electron microscope image of the framework-type non-precious metal catalyst of Example 1 of the present invention is shown.

[0023] Figure 4 A graph showing the relationship between current density and potential for examples of the present invention and comparative examples. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with examples. These examples are intended to better further understand the present invention, are not limited to the best mode of implementation, and do not limit the content and protection scope of the present invention. Any product that is the same or similar to the present invention and is obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts falls within the protection scope of the present invention.

[0025] It should be noted that, in the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. The experimental methods used in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial sources. The present invention will be described in detail below in conjunction with the embodiments.

[0026] The present invention provides a framework-type non-precious metal catalyst and a preparation method thereof, which are mainly applied in the field of catalysis and involve the fields of material synthesis, catalysis, hydrogen energy, etc. The present invention first prepares a composite of an organic metal framework (MOF) and a polyacid compound (POM), obtains a non-precious metal catalyst with a framework structure by annealing, and then forms a catalyst with a non-precious metal as the main body by ion exchange. The catalyst prepared by the method has a three-dimensional framework structure, a large active site density, a high specific surface area, and good catalytic performance and structural stability.

[0027] According to one aspect of the present invention, the present invention provides a framework-type non-precious metal catalyst comprising Cu x Fe yA WO4 framework catalyst, wherein x+y=1, preferably x is 0.7 and y is 0.3.

[0028] Cu x Fe y The framework catalyst of WO4 is a framework catalyst composed of copper (Cu), iron (Fe) and tungsten (W) oxides. Among them, Cu and Fe serve as active metal centers, W is a component of the framework, and O represents the oxygen element, which constitutes the main body of the oxide.

[0029] Copper is a cheap and readily available transition metal that has shown good catalytic performance in many fields. Its oxides have received extensive attention and applications in electrochemistry, photochemistry, photoelectrochemistry, and other fields. x Fe y In WO4, the active transition metal elements - copper and iron exist in an oxidized state, and their molar ratio will have a significant effect on the physicochemical properties of the oxide, and will further affect the catalytic performance of the oxide (including activity and selectivity). By adjusting the ratio of iron, the electronic structure of copper and iron will be adjusted, which will enhance its catalytic activity for reactions such as oxygen reduction and photoelectrolysis of water. Tungsten is mainly used as a structural component of the framework in the catalyst. Its high melting point and chemical stability enable it to maintain the structural stability of the catalyst under high temperature and corrosive conditions. The structural basis of metal-organic frameworks (COFs) and polyoxometalates (POMs) helps to form a three-dimensional framework structure with a high specific surface area, providing abundant surface sites for active metal centers. Oxygen elements form oxides with Cu, Fe and W, which are important components in the catalyst structure and affect the electronic environment of the metal center and the activity of the catalyst.

[0030] According to another aspect of the present invention, a method for preparing a framework-type non-precious metal catalyst is provided, the method comprising the following steps: S1: mixing and stirring a copper salt, L-glutamic acid and phosphotungstic acid or a hydrate thereof in a solvent to prepare a MOF@POM complex; S2: annealing the MOF@POM complex in an inert gas atmosphere to prepare a MOF@POM derivative; S3: dispersing the MOF@POM derivative in a trivalent iron salt solution for ion exchange to obtain a framework-type non-precious metal catalyst.

[0031] The present invention successfully constructed a new type of non-precious metal catalyst Cu through the preparation of MOF@POM composite and subsequent annealing, ion exchange and reduction process. x Fe y WO4. Figure 1The flowchart of the preparation method of the framework-type non-precious metal catalyst of the present invention is shown. Among them, the preparation of the complex corresponds to step S1, and in the schematic diagram below, the components are mixed and stirred in a solvent to prepare the MOF@POM complex; the preparation of the derivative corresponds to step S2, and in the schematic diagram below, the MOF@POM complex is annealed in an inert gas atmosphere to prepare the MOF@POM derivative, wherein the direction of the arrow indicates the direction of the inert gas flow; the ion exchange corresponds to step S3, and in the schematic diagram below, the MOF@POM derivative is dispersed in a trivalent iron salt solution, Fe 3+ The ions are embedded into the MOF@POM derivative framework through an ion exchange mechanism, replacing part of the Cu 2+ ; It is then used in catalytic applications. The three-dimensional framework structure of the present invention can optimize the coordination environment of the active metal center, improve the electron transfer path, and adjust the adsorption energy of key intermediates, ensuring the high performance of the catalyst in the catalytic reaction.

[0032] The copper salt can be selected from one or more of copper acetate, copper chloride, copper bromide, copper nitrate and their hydrates, preferably copper salt is selected from one or more of copper acetate and its hydrates; phosphotungstic acid or its hydrate preferably uses phosphotungstic acid hydrate, for example, phosphotungstic acid hydrate can be H6O 80 PW 24 ·xH2O (molecular weight 5760.11) or H3[P(W3O 10 )4]·xH2O (molecular weight 2880.05).

[0033] The solvent may be selected from at least one of methanol, ethanol, acetone and water; the ferric iron salt solution may be selected from one or more of ferric nitrate, ferric sulfate and ferric chloride.

[0034] According to one embodiment of the present invention, in step S1, the molar ratio of copper to L-glutamic acid is within the range of 0.8 to 1.3, preferably 0.95-1.05, and the composite framework within this range has good openness, while maintaining the stability of the structure, and has good framework construction efficiency. L-glutamic acid, as an organic ligand, combines with copper ions to form a MOF structure, and the fine adjustment of its ratio will affect the formation of the framework. If the molar ratio of copper to L-glutamic acid is too high, the framework structure may be too tight, limiting the embedding of POM molecules and subsequent ion exchange processes. On the contrary, if the ratio is too low, the framework structure may be incomplete, affecting the stability and catalytic activity of the composite. For example, the molar ratio of copper to L-glutamic acid can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3. The molar ratio of copper to L-glutamic acid can be selected from any of the above-mentioned points or any range values ​​therebetween.

[0035] The molar ratio of copper to tungsten is within the range of 0.9 to 1.25. Within this range, the distribution of active centers in the composite catalyst can be optimized and the catalytic performance can be enhanced. Phosphotungstic acid or its hydrate, as a source of polyoxometalates (POM), interacts with copper ions in the MOF framework to form a composite structure with catalytic activity and stability. The molar ratio of copper to tungsten determines the relative content of the two metal ions in the composite, thereby affecting the density and distribution of active sites. Too high or too low copper content is likely to weaken the stability of the framework structure, making it difficult to form the framework structure, thereby affecting the structural stability. The inventors have found that by regulating the mass ratio of copper to tungsten within the range of 0.9 to 1.25, the stable synthesis of the framework can be maintained, and a more obvious catalytic activity is exhibited. For example, the molar ratio of copper to tungsten can be 0.9, 0.95, 1.0, 1.05, 1.10, 1.15, 1.20, 1.25. The molar ratio of copper to tungsten can be selected from any of the above-mentioned points or any range value therebetween.

[0036] In addition, the distribution of copper ions in the MOF framework and the interaction with tungsten ions directly affect the electron transfer path of the composite catalyst. Copper, as the main conductive component, can effectively promote the flow of electrons; and the presence of tungsten ions in the POM structure provides an additional path for electron transfer. By optimizing the ratio of copper to tungsten, the electronic environment of the composite catalyst can be adjusted to promote the effective transmission of electrons. The precise regulation of active centers in the composite catalyst can also affect the adsorption capacity of key intermediates. For some catalytic reactions, the adsorption and desorption rates of intermediates determine the overall rate of the reaction. By adjusting the ratio of copper to tungsten within a certain range, the microstructure of the MOF@POM composite can be finely adjusted, and the adsorption capacity of intermediates on the catalyst surface can be adjusted, avoiding excessive adsorption of intermediates (leading to blockage of catalytic sites) or insufficient adsorption (leading to reduced catalytic efficiency), thereby ensuring the high efficiency of the catalytic reaction.

[0037] According to one embodiment of the present invention, in step S1, copper salt, L-glutamic acid and phosphotungstic acid or its hydrate are added to deionized water, wherein the concentration of copper is in the range of 0.01 mol / L to 0.03 mol / L; stirring is performed at room temperature (20-25°C), preferably the stirring time is 0.5 to 3 hours, more preferably 1 hour; an ethanol solution of trimesic acid is added to the above solution, and stirring is continued at room temperature (20-25°C), preferably the stirring time is 10 to 24 hours, more preferably 14 hours; the precipitate is collected, preferably by centrifugation or filtration; and then the precipitate is dried, preferably in a vacuum oven, preferably the drying temperature is 60°C to 80°C, and the drying time is preferably 10 to 16 hours.

[0038] For example, the concentration of copper can be 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L. The concentration of copper can be selected from any of the above values ​​or any range of values ​​therebetween. Preferably, the concentration range of copper is 0.025 mol / L.

[0039] Within the above copper concentration range, the equilibrium interaction between copper ions and L-glutamic acid and phosphotungstic acid or its hydrate molecules can be improved, which is beneficial to the formation of the MOF framework and the uniform embedding of POM.

[0040] Preferably, the concentration of the ethanol solution of trimesic acid is in the range of 0.01 to 0.03 mol / L. For example, the concentration of the ethanol solution of trimesic acid may be 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L. The concentration of the ethanol solution of trimesic acid may be selected from any of the above values ​​or any range of values ​​therebetween.

[0041] The molar ratio of trimesic acid to copper salt is in the range of 0.66 to 1. For example, the molar ratio of trimesic acid to copper salt can be 0.66, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1. The molar ratio of trimesic acid to copper salt can be selected from any of the above values ​​or any range of values ​​therebetween.

[0042] The present inventors found that the selection of the above concentration and molar ratio of trimesic acid as a structure-directing agent is beneficial to the construction of the MOF framework, and can ensure that the composite has a high specific surface area and good porosity, providing sufficient contact interface and reaction channel for the catalytic reaction. In addition, the above concentration and molar ratio are conducive to the formation of stable chemical bonds and pore structures, creating more active sites on the catalyst surface.

[0043] According to one embodiment of the present invention, in step S2, the MOF@POM composite is heated to 550-700°C, preferably 600-650°C, in an inert gas atmosphere at a heating rate of 2°C / min to 10°C / min; maintained for 1 to 5 hours; then cooled to room temperature at a rate of 2°C / min to 20°C / min; a MOF@POM derivative is obtained; preferably, the flow rate of the inert gas is in the range of 5 to 20 sccm.

[0044] Annealing the composite in an inert gas atmosphere can effectively prevent oxidation or reaction with other components in the air during high temperature treatment, thereby ensuring that the structural integrity and chemical stability of the composite are not damaged. Preferably, the inert gas atmosphere is selected from nitrogen or argon. The presence of nitrogen or argon can create an inert external reaction environment, prompting the composite to fully react and maintain the framework structure under a heating environment to avoid external interference. The heating rate of the present invention is conducive to the uniformity of structural transformation, and ensures the formation efficiency and quality of the derivative on the basis of maintaining the framework structure. For example, the heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The heating rate can be selected from any of the above points or any range value therebetween, preferably 5°C / min. The temperature holding time of the present invention is conducive to accelerating the transformation of the structure, promoting the perfection of the crystal phase, and avoiding structural damage or metal particle aggregation caused by high temperature treatment, thereby ensuring the structural stability and high activity of the derivative. For example, the temperature holding time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours. The time for temperature maintenance can be selected from any of the above-mentioned points or any range values ​​therebetween, preferably 2 hours. The control of the cooling rate of the present invention avoids structural stress caused by temperature changes, reduces defects in derivatives, and improves structural consistency and stability. For example, the cooling rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min. The cooling rate can be selected from any of the above-mentioned points or any range values ​​therebetween. The flow rate of the gas of the present invention provides sufficient gas protection and ensures uniform distribution of the atmosphere in the reaction vessel to avoid structural inconsistencies caused by different local atmospheres. For example, the gas flow rate can be 5sccm, 6sccm, 7sccm, 8sccm, 9sccm, 10sccm, 11sccm, 12sccm, 13sccm, 14sccm, 15sccm, 16sccm, 17sccm, 18sccm, 19sccm, 20sccm. The gas flow rate can be selected from any of the above values ​​or any range therebetween, preferably 10sccm.

[0045] According to one embodiment of the present invention, in step S3, a MOF@POM derivative is dispersed in a ferric iron salt solution, preferably the concentration of the ferric iron salt solution is 0.05M to 0.5M, and the concentration of the MOF@POM derivative in the ferric iron salt solution is 0.05g / L to 0.3g / L; stirring is performed for 30 to 80 minutes, preferably 40 minutes, preferably at a speed of 200rpm to 500rpm; the MOF@POM derivative is reduced to obtain copper particles while completing ion exchange to form a framework-type non-precious metal catalyst; a precipitate is obtained, preferably by filtration or centrifugation; the precipitate is washed, preferably with acetone or ethanol, preferably at least three times; the precipitate is dried, preferably in a vacuum oven, preferably at a drying temperature of 60°C to 80°C.

[0046] In step S3, the derivative is stirred to promote the reaction with Fe 3+ The copper ions in the derivative are fully contacted and evenly dispersed. Some of the copper ions in the derivative are reduced to form copper particles, while Fe 3+ The ions are embedded into the MOF framework through an ion exchange mechanism, replacing part of the Cu 2+ , forming Cu x Fe y WO4 composite catalyst. The solution concentration and derivative concentration of the present invention ensure the efficiency and selectivity of the ion exchange reaction and promote the formation of catalytic active centers. The collection and cleaning of the precipitate are intended to remove the residual solvent and reaction byproducts adsorbed on the surface of the catalyst, keep the catalyst clean and active, and improve its catalytic efficiency.

[0047] According to another aspect of the present invention, there is provided a framework-type non-precious metal catalyst, characterized in that the catalyst is prepared according to the method according to any one of claims 2 to 9.

[0048] The final catalyst product of the present invention mainly comprises Cu x Fe y WO4. However, during the preparation process, other substances used in the auxiliary preparation or ion exchange process may remain, such as incompletely reacted precursors (such as L-glutamic acid, trimesic acid (H3BTC), etc.), and solvents that may be used for subsequent treatment (such as acetone, ethanol). However, these residues are usually removed during the washing and drying steps, so the final product is mainly composed of Cu x Fe y WO4 composition.

[0049] In the field of catalyst design, in order to further optimize the performance of the catalyst, such as improving activity, selectivity, stability and durability, other optional components are often introduced as co-catalysts or carriers. These components may include one or more of the following:

[0050] Co-catalysts, such as other metal oxides (such as MnO2, CoO, etc.), metals (such as Ni, Co), non-metallic elements (such as N, S), etc., which can form alloys or complexes with the main catalyst, adjust the electronic structure of the catalyst, and enhance the catalytic performance;

[0051] Support, usually materials with high specific surface area are used as support, such as silica (SiO2), alumina (Al2O3), carbon nanotubes (CNTs), graphene, zeolite, etc. Support can not only provide additional surface sites, but also improve the thermal stability and mechanical strength of the catalyst, and promote the dispersion of the catalyst in the reaction medium;

[0052] Surfactants: During the catalyst preparation process, surfactants such as sodium dodecyl sulfate (SDS) and polyethylene glycol (PEG) may be used to control particle size and dispersibility. These substances are usually removed in subsequent steps; and

[0053] Stabilizers are used to maintain the stability of the catalyst structure during preparation or use, such as complexing agents or small molecule ligands, which can form a stable coordination structure with the metal center to prevent the aggregation or loss of metal particles.

[0054] In summary, Cu x Fe y The core components of WO4 framework catalysts are oxides of Cu, Fe and W, but in practical applications, to improve their performance, they may also contain co-catalysts, supports and other auxiliary components. These additional components can be selected and optimized according to specific application requirements and reaction conditions.

[0055] Catalysts need to withstand harsh conditions such as high temperature, high pressure or corrosive media in industrial applications. x Fe y The WO4 framework catalyst has excellent chemical stability, thermal stability and electrochemical stability, and can maintain high activity and selectivity in extreme environments, extend the service life of the catalyst, and reduce the replacement frequency and cost in industrial production. In addition, the catalyst of the present invention is comparable to precious metal catalysts in catalytic activity, selectivity and stability, and even surpasses them in some aspects, realizing high-value applications of non-precious metal materials.

[0056] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0057] Embodiment 1:

[0058] Weigh 200 mg of copper acetate dihydrate, 147 mg of L-glutamic acid, and phosphotungstic acid hydrate (H6O 80 PW24 ·xH2O, molecular weight 5760.11) 300 mg was dissolved in 40 mL of water and stirred with a magnetic stirrer (300 rpm) for 1 hour. After the above substances were fully dissolved and complexed, 40 mL of 3.5 g / L ethanol solution of trimesic acid (H3BTC, molecular weight 210.14) was added. After stirring with a magnetic stirrer (300 rpm) for 14 hours, the precipitate of the MOF@POM complex was obtained by suction filtration. The precipitate was washed with ethanol for 3 times and then dried in a vacuum oven at 75°C for 12 hours.

[0059] Subsequently, in an argon (10 sccm) environment, the temperature was first increased to 600°C at a rate of 5°C / min, maintained for 120 min, and then decreased to room temperature at a rate of 5°C / min to obtain a MOF@POM derivative. Figure 2 A scanning electron microscope (SEM) image of the MOF@POM derivative is shown.

[0060] The derivative was dispersed in a 0.1M ferric chloride solution with a derivative concentration of 0.1 g / L, stirred (300 rpm) for 40 minutes, and a precipitate was obtained by suction filtration. The precipitate was washed three times with ethanol and dried in a vacuum oven at 70°C to obtain Cu x Fe y WO4 framework catalyst. Figure 3 A transmission electron micrograph of the catalyst is shown.

[0061] Embodiment 2:

[0062] Weigh 200 mg of copper acetate dihydrate, 150 mg of L-glutamic acid, and phosphotungstic acid hydrate (H3O 40 PW 12 ·xH2O, molecular weight 2880.05) 300 mg was dissolved in 40 mL of water and stirred with a magnetic stirrer (300 rpm) for 1 hour. After the above substances were fully dissolved and complexed, 40 mL of 3.5 g / L ethanol solution of trimesic acid (H3BTC, molecular weight 210.14) was added. After stirring with a magnetic stirrer (400 rpm) for 14 hours, a precipitate of the MOF@POM complex was obtained by centrifugation. The precipitate was washed three times with ethanol and then dried in a vacuum oven at 75°C for 12 hours.

[0063] Subsequently, in a nitrogen (10 sccm) environment, the temperature was first increased to 600°C at a rate of 5°C / min, maintained for 120 min, and then decreased to room temperature at a rate of 5°C / min to obtain a MOF@POM derivative.

[0064] The derivative was dispersed in a 0.2 concentration of ferric acetate solution, the derivative concentration was 0.15 g / L, stirred (400 rpm) for 50 minutes, and a precipitate was obtained by centrifugation. The precipitate was washed three times with acetone and dried in a vacuum oven at 75°C to obtain Cu x Fe y WO4 framework catalyst.

[0065] Embodiment 3:

[0066] Weigh 200 mg of copper acetate dihydrate, 160 mg of L-glutamic acid, and phosphotungstic acid hydrate (H6O80PW 24 ·xH2O, molecular weight 5760.11) 300 mg was dissolved in 40 mL of water and stirred with a magnetic stirrer (300 rpm) for 1.2 hours. After the above substances were fully dissolved and complexed, 40 mL of 2 g / L ethanol solution of trimesic acid (H3BTC, molecular weight 210.14) was added. After stirring with a magnetic stirrer (300 rpm) for 9 hours, the precipitate of the MOF@POM complex was obtained by suction filtration. The precipitate was washed with ethanol for 3 times and then dried in a vacuum oven at 75°C for 14 hours.

[0067] Subsequently, in an argon (10 sccm) environment, the temperature was first increased to 600°C at a rate of 8°C / min, maintained for 120 min, and then decreased to room temperature at a rate of 10°C / min to obtain a MOF@POM derivative.

[0068] The derivative was dispersed in a 0.2% ferric acetate solution, the derivative concentration was 0.1 g / L, stirred (300 rpm) for 60 minutes, and a precipitate was obtained by suction filtration. The precipitate was washed three times with acetone and dried in a vacuum oven at 75 to obtain Cu x Fe y WO4 framework catalyst.

[0069] Comparative Example 1

[0070] Weigh 200 mg of copper acetate dihydrate, 147 mg of L-glutamic acid, and phosphotungstic acid hydrate (H6O 80 PW 24 ·xH2O, molecular weight 5760.11) 300 mg was dissolved in 40 mL of water and stirred with a magnetic stirrer (300 rpm) for 1 hour. After the above substances were fully dissolved and complexed, 40 mL of 3.5 g / L ethanol solution of trimesic acid (H3BTC, molecular weight 210.14) was added. After stirring with a magnetic stirrer (300 rpm) for 14 hours, the precipitate of the MOF@POM complex was obtained by suction filtration. The precipitate was washed with ethanol for 3 times and then dried in a vacuum oven at 75°C for 12 hours.

[0071] Subsequently, in an argon (10 sccm) environment, the temperature was first increased to 600°C at a rate of 5°C / min, maintained for 120 min, and then decreased to room temperature at a rate of 5°C / min to obtain a copper-based MOF@POM derivative that did not contain Fe elements.

[0072] Comparative Example 2

[0073] Weigh 200 mg of copper acetate dihydrate, 80 mg of L-glutamic acid, and phosphotungstic acid hydrate (H6O 80 PW 24 ·xH2O, molecular weight 5760.11) 150 mg. Then, Cu was prepared in the same manner as in Example 1. x Fe y WO4 framework catalyst.

[0074] Test methods and results:

[0075] The water electrolysis effects of Examples 1 to 3 and Comparative Examples 1 to 2 were evaluated, with the working electrode targeting oxygen evolution reaction (OER), i.e., water oxidation reaction, and the investigation index being current density.

[0076] The products obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were respectively dispersed by low temperature (<15°C) ultrasonic dispersion to obtain a 5 mg / mL water-isopropanol solution (water-to-alcohol volume ratio of 0.3); the solution was sprayed on the surface of a 3 mm glassy carbon electrode, and after drying, a layer of 0.05 wt% Nafion solution (Nafion: product mass ratio = 0.1) was added to the surface to obtain a 2 mg / cm 2 Loading amount of the working electrode.

[0077] The electrode is combined with Pt wire or carbon rod (cathode), Hg / HgO reference electrode and 1M KOH solution to form a three-electrode system for water electrolysis test.

[0078] The test results are as follows Figure 4 As shown, the current density of the catalysts of Examples 1 to 3 of the present invention at the same potential is significantly better than that of Comparative Example 1 (MOF@POM derivative without Fe element) and Comparative Example 2, which proves the feasibility of the catalyst preparation method of the present invention and the excellent effect of the catalyst prepared by the method of the present invention.

[0079] Through the detailed description of the above embodiments, it can be seen that the framework-type non-precious metal catalyst Cu x Fe yPreparation process and application range of WO4. Its unique framework structure and precise copper-iron ratio control not only improve the catalytic efficiency but also reduce the cost, which is of great significance to environmental protection and sustainable development. Under different reaction conditions, the high activity, high stability and good selectivity of the catalyst make it an ideal choice for a variety of chemical reactions. In addition, the catalyst's ability to be recycled and reused further proves its potential in industrial applications.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A framework-type non-precious metal catalyst, characterized in that: The catalyst comprises Cu x Fe y A WO4 framework catalyst, wherein x+y=1, preferably x is 0.7 and y is 0.

3.

2. A method for preparing a framework-type non-precious metal catalyst, characterized in that: The method comprises the following steps: S1: copper salt, L-glutamic acid and phosphotungstic acid or its hydrate are mixed in a solvent and stirred to prepare a MOF@POM composite; S2: annealing the MOF@POM composite in an inert gas atmosphere to prepare a MOF@POM derivative; S3: dispersing the MOF@POM derivative in a trivalent iron salt solution for ion exchange to obtain the framework-type non-precious metal catalyst.

3. The method according to claim 2, characterized in that In step S1, the molar ratio of copper to L-glutamic acid is in the range of 0.8 to 1.3, preferably 0.95-1.05, and the molar ratio of copper to tungsten is in the range of 0.9 to 1.25, preferably 1.1-1.

2.

4. The method according to claim 2 or 3, characterized in that: The copper salt is selected from one or more of copper acetate, copper chloride, copper bromide, copper nitrate and hydrates thereof, and preferably the copper salt is selected from one or more of copper acetate and hydrates thereof.

5. The method according to claim 2 or 3, characterized in that: The solvent is selected from at least one of methanol, ethanol, acetone and water.

6. The method according to claim 2 or 3, characterized in that: The ferric iron salt solution is selected from one or more of ferric nitrate, ferric sulfate and ferric chloride.

7. The method according to claim 2 or 3, characterized in that: In step S1, the copper salt, L-glutamic acid and the phosphotungstic acid or its hydrate are added to deionized water, wherein the concentration of copper is in the range of 0.01 mol / L to 0.03 mol / L, preferably 0.025 mol / L; stirring is performed, preferably the stirring time is 0.5 to 3 hours, more preferably 1 hour; an ethanol solution of trimesic acid is added to the stirred solution, preferably the concentration of the ethanol solution of trimesic acid is in the range of 0.01 to 0.03 mol / L, wherein the molar ratio of trimesic acid to the copper salt is in the range of 0.66 to 1; stirring is performed, preferably the stirring time is 10 to 24 hours, more preferably 14 hours; the precipitate is collected, preferably by centrifugation or suction filtration; and then the precipitate is dried, preferably in a vacuum oven, preferably the drying temperature is 60° C. to 80° C., and preferably the drying time is 10 to 16 hours.

8. The method according to claim 2 or 3, characterized in that: In step S2, the MOF@POM composite is heated to 550-700°C, preferably 600-650°C, in the inert gas atmosphere, preferably the inert gas atmosphere is selected from nitrogen or argon, at a heating rate of 2°C / min to 10°C / min, preferably 5°C / min; maintained for 1 to 5 hours, preferably 2 hours; then cooled to room temperature at a rate of 2°C / min to 20°C / min; the MOF@POM derivative is obtained; preferably the flow rate of the inert gas is in the range of 5 to 20sccm, preferably 10sccm.

9. The method according to claim 2 or 3, characterized in that: In step S3, the MOF@POM derivative is dispersed in the ferric iron salt solution, preferably the concentration of the ferric iron salt solution is 0.05M to 0.5M, and the concentration of the MOF@POM derivative in the ferric iron salt solution is 0.05g / L to 0.3g / L; stirring for 30 to 80 minutes, preferably 40 minutes, preferably stirring at a speed of 200-500rpm; reducing the MOF@POM derivative to obtain copper particles while completing ion exchange to form the framework-type non-precious metal catalyst; obtaining a precipitate, preferably by filtration or centrifugation; washing the precipitate, preferably using acetone or ethanol for washing, preferably washing at least three times; drying the precipitate, preferably drying it in a vacuum oven, preferably at a drying temperature of 60°C to 80°C.

10. A framework-type non-precious metal catalyst, characterized in that: The catalyst is prepared according to the method according to any one of claims 2 to 9.

11. The framework-type non-precious metal catalyst according to claim 10, characterized in that: The main component of the catalyst is Cu x Fe y WO4, wherein x+y=1, preferably x is 0.7 and y is 0.3.